An analysis of human trafficking as an emerging threat to human security: case of Zimbabwean women to Kuwait: 2010-2016 - Chikosa, Joyce Chiratidzo (Midlands State University, 2020)
The research investigated human trafficking as an emerging threat to human security with a special focus on the trafficking of Zimbabwe women to Kuwait between 2010 and 2016. The research was guided by the following objectives: to analyse human trafficking as an emerging human security threat with specific focus on the trafficking of Zimbabwean women to Kuwait during the period 2010-2016, to examine the dynamics surrounding the challenges encountered in curbing human trafficking as a human security threat in Zimbabwe and to offer scholarly policy recommendations on national strategic solutions in curbing human trafficking as a human security threat not only in Zimbabwe but at a regional and international level. The research distributed 50 questionnaires to 50 women, victims of human trafficking that had been rescued from Kuwait and returned home. The research also conducted 3 key informant interviews on an official from the Immigration Department of Zimbabwe, an official from the Ministry of Public Service, Labour and Social Welfare and an official in the Diplomatic Missions Department of the Ministry of Foreign Affairs of Zimbabwe. Among the findings of the research is that: Poverty is a significant factor that has made Zimbabwean women more vulnerable to human trafficking and contributed to the emergence of human trafficking as a human security threat. High unemployment and underemployment are significant factors that have made Zimbabwean women more vulnerable to human trafficking and contributed to the emergence of human trafficking as a human security threat. The weakness in law enforcement is a factor that has increased the potential for Zimbabwe women to be trafficked to Kuwait. The trafficking for sexual exploitation is one of the forms of human trafficking that have emerged as a human security threat for Zimbabwe women. None of the respondents experienced trafficking for body parts or for moving drugs or weapons. Personal security is one form of human security deprived or violated by human traffickers on Zimbabwe women who are trafficked to Kuwait. Health security is a form of human security that is violated or deprived of the Zimbabwe women trafficked to Kuwait. Political security is one of the human security facets violated or deprived of Zimbabwe women that are trafficked to Kuwait. Food security component of human security of the Zimbabwe women is violated during the stay in restricted conditions in Kuwait. Among the recommendations proffered by the research are: that the Zimbabwe Trafficking of Persons Act of 2014 be amended to define, as part of human trafficking, all forms of exploitation that arise from it to include domestic servitude, slave labour, sexual exploitation, deliberate starvation, physical assault and verbal insult, that all Zimbabwean embassies around the world have law enforcement attachés that deal primarily with issues to do with human trafficking of Zimbabwe nationals, that airlines present brochures of country profiles including risks to human security found therein to travellers who intend to visit those countries not as a means to discourage but to instil vigilance, that local law enforcement receives training and resources with which to combat the evolving and growing threat of human trafficking.